Who drives green innovations? Characteristics and policy implications for green building collaborative innovation networks in China. (June 2021) - Wang, Ge; Li, Yang; Zuo, Jian; Hu, Wenbo; Nie, Qingwei; Lei, Heqian
Abstract: The delivery of green buildings, as a good approach for reducing energy consumption, has yielded lots of innovative outcomes. The need to spark effective innovations has become crucial. Yet, there has been no systematic examination of the green buildings field. This study provides a novel network-based and longitudinal perspective for examining the innovative collaboration of different types of organizations. Secondary data were collected from 223 projects receiving Green Building Innovation Awards (GBIA) in China. By using the social network analysis (SNA) method, the following results were obtained. First, collaborative networks of green-building innovation exhibit a salient feature of being scale-free, indicating a trend of path dependence in partner selections. Second, compared with the degree and closeness centrality, the betweenness centrality of those core organizations is growing faster over time. Unexpectedly, consulting enterprises, rather than design institutes or universities, are inclined to act as "bridges" during the innovative collaboration process. Thirdly, the average number of collaborations per GBIA organization is similar to that of theoretical disciplines (e.g., mathematics) but lower than that of experimental disciplines (e.g., medicine). With decreases in transitivity over time, the heterogeneity of networks has increased and the connections among different organizations are relying more on a few key enterprises or institutions. On this basis, a policy framework is presented that incorporates four governance strategies: " deactivation, " " framing, " " mobilizing, " and " synthesizing. " The findings shed new light on the development of innovation networks and the alignment of strategic decision-makings to facilitate the transformation of energy consumption in the built environment. Highlights: Secondary data were collected from Green Building Innovation Awards in China. Green-building innovation networks exhibit a salient feature of being scale-free. Consulting enterprises are inclined to act as "bridges" in the innovation network. A policy framework is developed incorporating four types of strategies.